Using the right tools: Enhancing retrieval from marked-up documents. - Welty, Christopher; Ide, Nancy (Computers & the Humanities, 1999)
Discusses a frame-based representation system developed at AT&T Bell Laboratories called CLASSIC. Comparison between CLASSIC and knowledge representation (KR) systems; Functions of CLASSIC; Features of CLASSIC; Representation of SGML documents in CLASSIC; Development of a set of principles for document type definition design; Benefits of using CLASSIC.